On a thermodynamically-balanced humidification-dehumidification desalination system driven by a vapor-absorption heat pump. (15th June 2021) - Elbassoussi, Muhammad H.; Ahmed, M.A.; Zubair, Syed M.; Qasem, Naef A.A.
Highlights: A novel balanced HDH system driven by an absorption unit is studied. Both single- and double-effect absorption heat pumps are considered. It is found to produce above 135 kg/h of desalinated water at a GOR > 10. The maximum COP value of 0.81 is recorded for the double-effect system. Thermodynamic balancing enhances GOR > 100% over the base HDH system. Abstract: A novel hybrid system consists of an efficient humidification-dehumidification (HDH) desalination unit driven by an absorption (AB) heat pump. A thermodynamically-balanced HDH unit with multiple air extractions is used, while single- and double-effect absorption (SEAB and DEAB, respectively) heat pumps are considered. The proposed systems are examined for simultaneous production of desalinated water and cooling effect under a fixed cooling load of 5 kW. As observed, the SEAB-HDH unit can produce up to 152.4 kg/h of desalinated water at a GOR value of around 10, for 0.002–0.0058 $/l. While the DEAB-HDH system delivers water of up to 135.4 kg/h for 0.0026–0.0098 $/l, at a GOR value approaching 15. Besides, COP values of about 0.50 and 0.81 are recorded for the SEAB- and the DEAB-HDH systems, respectively. It is noted that the DEAB-HDH system always supersedes the SEAB-HDH system in both GOR and COP values. An enhancement of over 100% in the GOR value is observed when air extraction is applied. Also, it is noted that single and double extractions improve water production by about 110 and 90%, respectively. A jump of nearly 500% is recorded in the water production when the cooling capacity increases from 2 to 15 kW. This jump is accompanied by a rise of 60 and 80% in the GOR and COP values, respectively. Finally, the theoretical GOR limit of the proposed systems is estimated.